A prototype of student attendant system using pocket PC approach / Mohd Nazim Nagib - Nagib, Mohd Nazim (2005)
Nowadays, electronic information spaces are encroaching on our everyday environment. It is because of the increasing number of mobile computing devices, such as pahntop computers, mobile phones and personal digital assistants. We are increasingly carrying electronic information with us and also tapping into reservoirs of information via access stations such as auto teller machine and telephone. Indeed, portable computing allow us not only to carry the information, but also to access, modifying and interact with it in a matter of second.